Why waste plastic bags? Choose reusable bags! : promotional campaign - Li, Melissa Shiying (2008)
This campaign aims to seek cooperation from Singapore’s stakeholders, the ‘People’, ‘Public’ and ‘Private’ enterprises to collectively stamp out excessive plastic bag wastage in Singapore.